Implementation of SDG 14 and Blue Economy Policies in Southeast Asia: A Comparative Policy Review - Alamsyahbana, Muhammad Isa; Chartady, Rachmad (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study explores the implementation of Sustainable Development Goal (SDG) 14 and blue economy policies across Southeast Asia, focusing on seven key indicators: protection of marine Key Biodiversity Areas (KBAs), waste management effectiveness, exploitation of fish stocks, use of destructive fishing gear, bycatch levels, marine biodiversity threats from imports, and national/regional policy efforts. Using a qualitative descriptive approach and secondary data analysis from international reports, national regulations, and scholarly sources, the study uncovers stark disparities among countries. High-capacity states like Indonesia, Malaysia, and Singapore have made measurable progress, whereas Least Developed Countries (LDCs) such as Laos, Cambodia, and Myanmar face significant implementation challenges due to limited financial, technological, and institutional resources. Findings indicate that overfishing, ineffective enforcement of trawling bans, lack of incentives for selective fishing gear, and ecological degradation from aquaculture expansion remain major concerns. However, emerging policy innovations such as Indonesia’s Sea Toll initiative, the Philippines’ coral reef ecotourism, and Singapore’s carbon taxes offer potential models. Still, these efforts are insufficient without greater regional harmonization, capacity building, and strategic resource redistribution. This study emphasizes the urgency of coordinated regional action, enhanced policy coherence, and inclusive support mechanisms to realize a sustainable, equitable, and resilient blue economy in Southeast Asia